Cancer in pregnancy. Part II: treatment options of breast and other non-gynecological malignancies - Hoellen, Friederike; Reibke, Roland; Hornemann, Katrin Emma; Thill, Marc; Luedders, Doerte W.; Kelling, Katharina; Hornemann, Amadeus; Bohlmann, Michael K. (Archives of gynecology and obstetrics, 2011)
In case of non-gynecological solid tumors and hematological malignancies diagnosed during pregnancy, individual diagnostic and treatment options must be established by an interdisciplinary team.